Narrative and Narrativity in Ancient Egypt Case Studies on Narrative Difference in Various Media - Moers, Gerald (Lingua Aegyptia Studia Monographica, 2023)
The volume collects the result of the project Altägyptische Erzählungen in Texten und Bildern: Ägyptologische Perspektiven auf zentrale Axiome einer historischen Text- und Bildnarratologie. It presents a sound methodological perspective for an analysis of the medial diversity and the historical uniqueness of the Ancient Egyptian narrative culture at the interface of contemporary narratological theories and Egyptological practise. A methodological introduction by Gerald Moers and four case studies on categories of narrative artefacts as diverse as texts, images, and tombs argue in favour of appropriately adjusting narratological theories - instead of just using them - with respect to the historically specific differences of the Egyptian narrative behaviour. Based on a cognitive approach that defines human experience as generally framed in a narrative manner, the contributions define narrative as a phenomenon that is neither restricted to nor defined by one medium that would be considered paradigmatically narrative. The study by Camilla di Biase-Dyson on the Egyptian term s.Dd, which has so far been understood as to refer to linear verbal narrative, argues for a much more complex and sophisticated semantics of the term as defining a specifically Egyptian understanding of what narrative is. In a similar manner, the analysis of certain spells from the Pyramid Texts by Kristina Hutter and Dina Serova establishes the existence of narrative coherence in a genre of texts that has so far been considered as being non-narrative by definition. The study of Claus Jurman on Old Kingdom tombs shows that their integrated compilation of texts, images, statuary, and architecture results in non-linear but complex multimodal narratives. Gerald Moers, in his analysis of exemplary genre-scenes from Ramesside ostraca, shows that even some so-called monochronic images that depict precisely one moment in time and have thus traditionally been said to be a-temporal and non-narrative by definition, often have a clearly structured temporal program and can thus be considered autonomous narratives.